Mycorrhizal symbiosis increases the benefits of plant facilitative interactions. Issue 3 (29th August 2018) - Montesinos‐Navarro, Alicia; Valiente‐Banuet, Alfonso; Verdú, Miguel
Abstract : The diversity of pathways through which mycorrhizal fungi alter plant coexistence hinders the understanding of their effects on plant‐plant interactions. The outcome of plant facilitative interactions can be indirectly affected by mycorrhizal symbiosis, ultimately shaping biodiversity patterns. We tested whether mycorrhizal symbiosis enhances plant facilitative interactions and whether its effect is consistent across different methodological approaches and biological scenarios. We conducted a meta‐analysis of 215 cases (involving 21 nurse and 29 facilitated species), in which the performance of a facilitated plant species is measured in the presence or absence of mycorrhizal fungi. We show that mycorrhizal fungi significantly enhance plant facilitative interactions mainly through an increment in plant biomass (aboveground) and nutrient content, although their effects differ across biological contexts. In semiarid environments mycorrhizal symbiosis enhances plant facilitation, while its effect is non‐significant in temperate ecosystems. In addition, arbuscular but not ecto‐mycorrhizal (EMF) fungi significantly enhance plant facilitation, particularly increasing the P content of the plants more than EMF. Some knowledge gaps regarding the importance of this phenomenon have been detected in this meta‐analysis. The effect of mycorrhizal symbiosis on plant facilitation has rarely been assessed in other ecosystems different from semiarid and temperate forests, and rarely considering other fungal benefits provided to plants besides nutrients. Finally, we are still far from understanding the effects of the whole fungal community on plant‐plant interactions, and on plant species coexistence.